Evaluating the impact of airborne radionuclides caused by the Fukushima nuclear accident on China based on global atmospheric dispersion. (September 2021) - Tang, Zhihong; Jiang, Suxiang; Cai, Jiejin; Li, Qiong; Li, Xuezhong; Gong, Ziqi
Abstract: In response to the Fukushima nuclear accident in Japan, the Comprehensive Nuclear-Test-Ban Treaty Organization (CTBTO) and other countries have conducted extensive monitoring and research. This article used an improved global atmospheric dispersion model WRF-Chem to simulate the global transport of radioactive materials released by the Fukushima nuclear. And mainly analyzed its impact on China, using the monitoring data of the environmental protection department to analyze the environmental level of atmospheric radioactivity and evaluate the model. The results showed that the radioactive plume spread from west to east, across the Pacific Ocean, the American continent and Europe, and finally, it spread to the entire northern hemisphere. China first detected I-131 in Heilongjiang Province on March 23, and until April 3, all provinces in China detected radionuclides from Fukushima nuclides. Combining the time taken by the radioactive plume to reach various parts of China, it can be inferred that the radioactive material can reach China through three routes, which may be the main reason why the leaked nuclides reach China and Europe in the same time. The global proliferation model tested by the FDNPP accident can provide a reference for the potential radiation impact of nuclear power plants, help understand the potential threat of future nuclear accidents, and provide support for nuclear accident monitoring and emergency measures.